Trade-based measures of international competitiveness and the identification of export opportunities - Tong, Violet Ming Hwee (2012)
International competitiveness is very significant to nations or countries because it is a ‘revealed’ measure of how a particular country is performing in the market they are competing in. In addition, international competitiveness analysis provides crucial information about the market of interest. It can generally be divided into trade-based approach (the focus of this study) and non trade-based approach. At present, the number of factors (variables) as indicators of international competitiveness is voluminous in the international trade literature. The most widely employed measure of international competitiveness when it comes to international trade is the RCA pioneered by Balassa (1965). The search for appropriate indicators of international business competitiveness remains an integral part of business research. However, there is a strand in the literature of international business which utilizes the BRCA (Balassa RCA) index to measuring international competitiveness which are Traill and Da Silva (1996) and Ibeh and Wheeler (2005). In this study, we would like to contribute by proposing a generalizable measure to measure international competitiveness that is fitted to country, industry or firm level. This new measure proposed is based on the geometrical methodology introduced by Azhar and Elliott (2008) which improves on the traditional RCA (Balassa, 1965) measure. The general geometry measure applicability is then tested on one of an important Malaysia export industry; which is the non-renewable energy industry. Four RCA measurement tools, BRCA (Balassa, 1965), ARCA (Hoen and Oosterhaven, 2006),and generalized GRCA (Azhar and Elliott, 2008) were used to investigate international competitiveness. The empirical illustration will be tested on Malaysia vis-à-vis its top exporting countries (namely Japan, Singapore, Korea and Australia) from year 2005-2010 using data from UNCOMTRADE database. The outcomes of the analysis are then plotted for Malaysia’s commodity export specialization. Results shows that in terms of international competitiveness ranking, the four measurement tools used do not differ much. Malaysia is most competitive in exporting HS271111 to Japan (2005 and 2010); HS271011 and HS271111 to Korea (2010); HS 270900 to Singapore (2010); and, HS270900 to Australia (2010). For products in which the country has no competitive edge at all, Malaysia should try avoiding exporting it or re-shuffle their strategy. The identification of export opportunities is essential as it aids existing and new exporters in deciding which market to invest in. This ensures that exporters fully realize their money’s worth when investing in the global market. The new measure is further extended to the identification of export opportunities. Similar to international competitiveness, identification of export opportunities has its own sets of measurement tools in the literature. They are shift-share model, decision support model, global screening model, trade-off model and ITC’s multi criteria model just to name a few. From the various tools in the literature, this study singles out the decision support model (DSM) by Cuyvers et. al. (1995). DSM uses a great deal of BRCA measure in its filters. In total 3 out of 4 filters uses the BRCA measure. Setting BRCA’s advantage aside, the traditional measure has many flaws. Thus, the new measure is designed and constructed in a way it can be extended to the DSM filters to identify export opportunities. A brief empirical illustration using rubber products on existing and new DSM filters was done to test its applicability. The result indicates major difference between the existing and new filters. This difference can be seen in the calculations, difference in market and its scope.